Effects of Ag Addition on Hot Deformation Behavior of Cu–Ni–Si Alloys1 . Issue 3 (18th January 2017) - Sun, Huili; Zhang, Yi; Volinsky, Alex A.; Wang, Bingjie; Tian, Baohong; Song, Kexing; Chai, Zhe; Liu, Yong
Abstract : Hot deformation behavior of Cu–Ni–Si and Cu–Ni–Si–Ag alloys is investigated using the Gleeble‐1500D simulator in the 600–800 °C deformation temperature and 0.01–5 s −1 strain rate ranges. Dynamic recrystallization (DRX) mechanism is a feature of high temperature flow stress–strain curves of the alloy. Microstructure is observed by optical microscopy. Ag addition can refine the grains and accelerate dynamic recrystallization. Characteristic points of the flow stress curves, including critical strain for DRX initiation (ϵc ), are determined by employing strain hardening rate analysis. Processing maps are developed and analyzed based on the dynamic material model (DMM). Ag addition can optimize the alloy processing workability. Abstract : Hot deformation behavior of Cu–Ni–Si and Cu–Ni–Si–Ag alloys is investigated. Dynamic recrystallization (DRX) mechanism is a feature of high temperature flow stress–strain curves of the alloy. Ag addition can refine the grains and accelerate dynamic recrystallization. Processing maps are developed and analyzed based on the dynamic material model (DMM). Ag addition can optimize the alloy processing workability.